PEMBUATAN WEBSITE AKADEMIK PADA SEKOLAH SMA BETHEL KOSAMBI - Felix Juan (Fakultas Teknologi Informasi Universitas Tarumanagara, 2016)
The goal for this academic website to provides an overview how academic website looks like at a school, how academic website works, and the level of effectiveness that can be achieved in the teaching and learning activities in school. Besides the benefits of making this academic websites that facilitate students in making the target value to be achieved for the following semester, facilitate the student to see the timetable, exams, and grades, and also can be an alternative if the daily test results missing. For the teacher's academic website is useful for entering a grades, and see the teaching schedule. Academic website design methodology used the System Development Life Cycle (SDLC).